Syarie lawyer in federal territories: the admission requirements and process - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Malaysia Sdn. Bhd., 2025)
This Chapter discusses the admission requirements to be a Syarie lawyer or Peguam Syarie in the Syariah Courts with special focus on the Federal Territories pursuant to the Syarie Legal Profession (Federal Territories) Act 2019, a statute passed by Parliament for the Federal Territories in relation to Syarie matters enumerated in List II of the Ninth Schedule to the Federal Constitution.